Professional Education Management and Socio-Institutional Reality: problems and challenges - Eduardo Pinto e Silva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2008)
The democratic management of educational practices is a theoretical and practical matter, which has been discussed in several institutional spheres (PARO, 2003; BORGES, GIUBILEI & OLIVEIRA, 2006). This paper deals with education management and is based on a case study about technical and professional education of agents of Municipal Guard (SILVA, 2005). This kind of education is affected by structural problems in the public institution (SANTOS, 1987) and in the macro judicial system (PINHEIRO, 1997), also being harmed by a process of social and work precariousness (ANTUNES, 1999; 2005). All these aspects represent challenges that have to be overcame. Thus, our propose of democratic professional education management (SILVA, 2005; HELOANI & SILVA, 2006) opposes the bureaucratic and alienating management. It demands listening to the collective subject and assuming a reflexive praxis about the professional activities and the socio-institutional reality. We consider that the challenge of creating a democratic professional management and a critical collective conscience, articulated with innovative actions, is part of a horizon of possibilities, even when it is mediated by institutional, organizational and cultural dimensions (SILVA JÚNIOR & FERRETTI, 2004).